The impact of a model-based clinical regional registry for attention-deficit hyperactivity disorder. (September 2017) - Zanetti, Michele; Cartabia, Massimo; Didoni, Anna; Fortinguerra, Filomena; Reale, Laura; Mondini, Matteo; Bonati, Maurizio
This article describes the development and clinical impact of the Italian Regional ADHD Registry, aimed at collecting and monitoring diagnostic and therapeutic pathways of care for attention-deficit hyperactivity disorder children and adolescents, launched by the Italian Lombardy Region in June 2011. In particular, the model-based software used to run the registry and manage clinical care data acquisition and monitoring, is described. This software was developed using the PROSAFE programme, which is already used for data collection in many Italian intensive care units, as a stand-alone interface case report form. The use of the attention-deficit hyperactivity disorder regional registry led to an increase in the appropriateness of the clinical management of all patients included in the registry, proving to be an important instrument in ensuring an appropriate healthcare strategy for children and adolescents with attention-deficit/hyperactivity disorder.